Conceptual Joining Wood Structures from Detail to Utopia / Holzstrukturen im Experiment - Allner, Lukas; Kaltenbrunner, Christoph; Kröhnert, Daniela; Reinsberg, Philipp (Edition Angewandte, 2021)
This book explores experimental approaches to the design and construction of wooden structures in architecture, while presenting the results of an artistic research project. By using digital tools, experimental formations are created that are derived from the material logic. Selected guest contributions round up the documentation of the work processes.